Integration of urban agriculture Into community development for residential areas of Pasig City - Mercado, Victoria Hannah M. (College of Architecture, University of the Philippines Diliman, 2022)
The recent Covid-19 pandemic has pushed residents and city governments to consider urban agriculture as an option to strengthen food security in the urban area. Pasig City has taken interest in this industry and started forming community gardens as a way to provide an additional food source to the immediate residents. However, due to the lack of established spaces and programs to introduce urban agriculture, and the limitations on encouraging residents to initiate the activity in their communities, the popularity of urban agriculture has been slow and limited to government projects that give incentives to residents. My project aims to address the growing need for the development of urban agriculture as a practice to mitigate food insecurity in Pasig City, the need for spaces that can accommodate farming activities in public spaces, and to educate residents on how they can develop urban agriculture in their own communities. I will specifically be looking into how the community can be engaged through the provision of these spaces and how the activities can be adapted into their neighborhood as a way to encourage a sustainable, communal mindset that can benefit the residents in terms of food security. The project proposes that the development of public spaces and parks can consider the inclusion of urban agriculture as a communal food source and learning space to initiate its growth in residential areas. In conclusion, the project aims to present how urban agriculture can be assimilated into residential communities by introducing it as a sustainable way of strengthening food security, and integrating in the design of public spaces to promote its development in residential areas.